Предмет: Алгебра,
автор: Аноним
Знайдіть корінь рівняння (x-4)(x-6)-(x-2)(x+2)=-2
Ответы
Автор ответа:
0
Ответ: 3
Автор ответа:
0
(x-4)*(x-6) - ( x-2)*(x+2)= -2
(x^2-6x-4x+24) -( x^2+2x-2x-4)= -2
(x^2 -10x+24)-( x^2-4) = -2
x^2-10x+24-x^2+4= -2
-10x+28= -2
-10x= -2-28
-10x= -30
x= 3 .
Ответ: x= 3 .
Похожие вопросы
Предмет: Физика,
автор: HedgehodSonic
Предмет: Математика,
автор: danilamihalicin
Предмет: Українська мова,
автор: yana61507
Предмет: Математика,
автор: rook732
Предмет: История,
автор: kkv